PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS DENGAN MENGGUNAKAN COOPERATIVE LEARNING TIPE THINK PAIR SHARE DI SEKOLAH DASAR - Irma, Ade (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This research base of fact in that field study of social studies in Class V SD Negeri 09 VII Koto Sungai Sariak. Teacher studies still predominate process and can not entangle student participation directly. The condition of lower makeup result result of learning study of IPS as roomates According to chief engineer have been specified that is 75. Therefore not conducted by research with an aim to increase of IPS result of learning by using Model Cooperative Learning Type Think Pair Share of According to Frank (in Yatim, 2010:274) in Class V SD Negeri 09 VII Koto Sungai Sariak. Approach that use qualitative research and is quantitative, while this Type of research that is Research Action Class (PTK) with this device cover research, (1) planning, (2) execution, (3) perception / observation, and (4) reflection. Result of research be result of RPP grow up, execution, and result student learn. Become study can be concluded that by using models of IPS Cooperative Learning Type Think Pair Share can improve V Elementary School learn result 09 VII Koto Sariak River Kata Kunci: hasil belajar IPS dan cooperative learning tipe think pair share